A decisão do Supremo Tribunal Federal no julgamento da ADPF 132 e da ADI 4.277 à luz da teoria de Robert Alexy - Renato Alves Ribeiro Neto (2015)
This dissertation assessed the role played by the Brazilian Supreme Court (STF) and the quality of the judicial review, requested through ADPF 132 and ADI 4.277, in which the court unanimously recognized same-sex unions as legal, under the articles 226, §3º, of the Federal Constitution, and 1.723 of the Civil Code. Robert Alexy theory of the constitutional rights and legal discourse was used as main theoretical reference, complemented by the works of Trivisonno, Barroso and Lopes. The study focused the review of the legal arguments presented to and by the court and also of the role played by court considering the social expectations and constitutional boundaries involved. A historical and comparative background of the condition of gay rights in Brazil was established, assessing the success of the organized homosexual movement in reinterpreting the position and the identity of the group in the Brazilian culture, which generated relevant legal and political impacts. The main arguments presented by the Court were thoroughly analyzed; a distinction was made between the (winning) “extensive interpretation thesis” and the (dissident) “gap integration by analogy thesis”; and level of rationality of the decision was evaluated. The role played by the STF and how it affected the balance between the Judicial branch and the Legislative branch were analyzed. The study concluded that the efforts of the organized homosexual groups have been successful in its campaign for recognition and equality, and also that the adjudication rendered by the Supreme Court represented a great democratic achievement. It also concluded that the “gap integration by analogy thesis” would be a more reasonable solution for the case, because it would still recognize the same substantial rights to the same-sex unions, without interfering profoundly with the “constitutional dynamics” strongly expressed in the precedents of the Court, especially in the ADI 815-3. The “extensive interpretation thesis”, adopted by the Court, would also be reasonably defensible, but the arguments effectively presented to support it were not enough to overcome the heavy argumentative burden imposed over the judicial review by clear and irrefutable determinations of the original creators of the Brazilian Constitution. Such absence of sufficient reasons in support of the decision made indicate that the Court invaded the area of discretion of the legislator. Finally, despite the unquestionable legal advance that the decision promoted regarding equality and recognition of a minority, the activist role declaredly assumed by the Court affected the institutional balance negatively and left a dangerous legacy of arbitrariness and judicial subjectivity.